The foraging zones of breeding royal (Eudyptes schlegeli) and rockhopper (E-chrysocome) penguins: an assessment of techniques and species comparison - Hull, CL (1999)
This study used VHF telemetry, time-depth recorders (TDRs) collecting geolocation and sea-surface temperature data, and foraging-trip durations to describe and compare the foraging zones of royal and rockhopper penguins at Macquarie Island. VHF telemetry was unsuccessful, but TDRs were deployed 61 times across the four stages of the breeding season (males during incubation, females during incubation, guard stage and creche stage) during the 1994/95 and 1995/96 austral summers, with 37 providing data for analysis. The errors inherent in geolocation made it impossible to determine precise foraging zones and overlaps between the species. However, sea-surface temperature data and foraging-trip durations provided estimates of foraging zones. Both species foraged in waters of the same temperature (6.8-10.8Â°C), representing the same regions of the polar frontal zone. It was estimated that rockhopper penguins did not travel as far as royal penguins, providing some degree of segregation in foraging zones. When the data were assessed contemporaneously, to take into account the 3-week asynchrony in the breeding season of the species, the overlap in foraging zones was small.